THE STUDENTS' PERCEPTION ON THE USE OF PADLET IN IMPROVING WRITING SKILLS - Shifa Nur Fadillah (Universitas Wiralodra, 2021)
Technology use in teaching and learning process had become very popular especially in the 21st century. Padlet is one of online platforms which have simple design and well-integrated features to support learning process. The implementation of Padlet turns the learning process becomes students-centered. This study discusses the use of Padlet in improving students’ writing skills. It mainly describes how the Padlet affect students’ interest in the learning process especially writing. This study is a qualitative research which using questionnaires to gather the data. The questionnaires given to students are divided into two types, namely yes-no question and yes-no question with reason. Students were given six questions related to their experience in using Padlet. Based on the results, most of students agree that the implementation of Padlet in writing class can improve their interest and writing skills. Students give positive responds towards the use of Padlet because of the great features provided in Padlet and immediate feedback they get from teacher and peers.